Efecto del extracto etanólico de hojas de annona muricata (guanábana) en la estabilización de especies radicalarias de oxígeno - Avalos Murga, Sandra Patricia (2015)
This research aims to determine the antioxidant capacity of the ethanol extract of leaves of Annona muricata. For which the leaves of this plant were collected in the city of Trujillo, selected sample, drying oven and proceeded to crushing, then the ethanol extract was prepared at different concentrations of 10, 20, 30, 40 and 50% V / V, with these systems which are faced with an aliquot of DPPH* were developed. Subsequently each of 3 absorbance readings was performed in Jenway spectrophotometer, at 517 nm; with this data the amount of DPPH* that reacts with the extract at 0 and 30 minutes was calculated. The effect of ethanol extract of Annona muricata is from the city of Trujillo has stabilizing effect of oxygen radical species